2022
DOI: 10.1038/s41598-022-11011-3
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotoxicity evaluation and proteomic analysis in kidneys of rats exposed to thioacetamide

Abstract: Thioacetamide (TAA) was administered orally at 0, 10, and 30 mg/kg body weight (BW) daily to Sprague–Dawley rats aged 6–7 weeks for 28 consecutive days. Nephrotoxicity and proteomics were evaluated in the kidneys of rats exposed to TAA. The BW decreased, however, the relative kidneys weight increased. No significant histopathologic abnormalities were found in the kidneys. The numbers of monocytes and platelets were significantly increased. However, the mean corpuscular volume and hematocrit values were decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 71 publications
(71 reference statements)
0
2
1
Order By: Relevance
“…Besides its toxic effects on the liver, TAA is known to cause blood abnormalities, lipoprotein abnormalities [ 37 ], and kidney disorders [ 38 ]. Contrary to the present study, studies have reported that TAA causes a decline in the levels of RBCs and HB and an increase in WBC levels due to acute inflammation in response to chemicals such as TAA [ 39 , 40 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Besides its toxic effects on the liver, TAA is known to cause blood abnormalities, lipoprotein abnormalities [ 37 ], and kidney disorders [ 38 ]. Contrary to the present study, studies have reported that TAA causes a decline in the levels of RBCs and HB and an increase in WBC levels due to acute inflammation in response to chemicals such as TAA [ 39 , 40 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, fusion of cell margins, vascular degeneration and pyknotic nuclei were observed in the renal glomeruli and tubules after treatment with 0.3% of TAA in drinking water for two weeks [ 1 ]. However, no significant histopathologic abnormalities were detected in the kidneys of rats exposed to oral TAA at doses like 10 mg and 30 mg/kg body weight for four weeks or intraperitoneal injection with 25 mg/kg or 100 mg/kg body weight for 8 or 24 hours [ 9 , 41 ]. In previous research, TAA increased collagen deposition and induced glomerular sclerosis and necrosis with interstitial fibrosis [ 2 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, all the measured oxidative stress markers (MDA, SOD and GSH) and proinflammatory cytokines like TNF-α were markedly affected by TAA treatment. Several studies reported the disturbance in the renal function parameters, oxidative stress markers, cytokines and inflammatory markers as interleukins in the TAA-treated group [ 1 , 2 , 9 - 12 , 41 ]. Mostly, oxidative stress plays the most important role in TAA-induced nephrotoxicity so that many authors hypothesized that the use of antioxidants could have beneficial effects [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%